The witch hunter's tale : a midwife mystery - Thomas, Samuel S. (Minotaur Books, 2015)
"Winter has come to the city of York, and with it the threat of witchcraft. As women and children sicken and die, midwife Bridget Hodgson is pulled against her will into a full-scale witch-hunt that threatens to devour all in its path, guilty and innocent alike. Bridget--accompanied once again by her deputy Martha Hawkins and her nephew Will Hodgson--finds herself playing a lethal game of cat and mouse against the most dangerous men in York, as well as her sworn enemy Rebecca Hooke. As the trials begin, and the noose begins to tighten around her neck, Bridget must answer the question: How far will she go to protect the people she loves?"--